2018
DOI: 10.1037/pro0000176
|View full text |Cite
|
Sign up to set email alerts
|

Technology as a means to address disparities in mental health research: A guide to “tele-tailoring” your research methods.

Abstract: We must include rural participants in health-related research if we are to address health-related disparities and inequity, particularly in mental health. However, the first step of the research process, in person, witnessed, signed informed consent is often a limiting factor and insurmountable barrier to precisely the type of research (e.g., telehealth) designed to overcome barriers of geographic distance and travel time. Telehealth, or the provision of medical care or services to patients by means of audio/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Finally, the reported demographics of included studies showed a prevalence of educated, white female participants [ 39 , 40 , 42 , 43 , 45 , 47 , 50 , 53 , 55 ]. Whilst this is a representative reflection of current research practice, the recommendations for best practice generated from this review allow the opportunity for future widespread integration of a standardised e-consent process [ 75 , 76 ] that could facilitate improved diversity in research and subsequently enable further exploration of e-consent use in underrepresented populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reported demographics of included studies showed a prevalence of educated, white female participants [ 39 , 40 , 42 , 43 , 45 , 47 , 50 , 53 , 55 ]. Whilst this is a representative reflection of current research practice, the recommendations for best practice generated from this review allow the opportunity for future widespread integration of a standardised e-consent process [ 75 , 76 ] that could facilitate improved diversity in research and subsequently enable further exploration of e-consent use in underrepresented populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, e-Consenting frameworks can be bolstered by teleconsent. While viewing the e-Consent materials in real time, potential participants and their parents/guardians may complete informed assent and consent with research staff over the phone ( López et al., 2018 ; Welch et al., 2016 ). Once completed, designated research support staff and the participants can be emailed a secure PDF of the signed assent/consent for their records.…”
Section: Ongoing Researchmentioning
confidence: 99%
“…O ne key factor in reducing health disparities is to increase access to health care services, particularly among vulnerable and underrepresented populations such as ethnic minorities and residents living in rural or provider shortage areas. 1 Shortage areas are identified as areas with too few primary care, dental, and mental health care providers or services. In the United States, 81 million people live in primary care Health Professional Shortage Areas (HPSAs) and 120 million people live in mental health care HPSAs.…”
Section: Introductionmentioning
confidence: 99%